Correlates of frailty in Alzheimer's disease and mild cognitive impairment. - LAWLOR, BRIAN; CUNNINGHAM, CONAL; WALSH, JAMES (My University, 2011)
The global prevalence of dementia is rising with Alzheimer's disease (AD) accounting for 50–60% of all cases and mild cognitive impairment (MCI) its precursor [1, 2]. Although the clinical hallmark of AD is progressive loss of memory and cognition, several studies have also shown changes in mobility and body composition suggesting frailty [3, 4]. Frailty represents age-related reduction in physiological reserve and resistance to stressors that can be delineated from comorbidity [5, 6]. It infers increased risk of health decline, disability and mortality regardless of concurrent illnesses. Intervention in the early stages may lead to reversal of frailty and prevent some of its adverse outcomes [6]. Individual components of frailty; impaired grip strength, slowed gait and low body mass index (BMI), have been shown to predict development of dementia and are associated with incident MCI [7–10]. The frailty syndrome within cognitively impaired patients may represent an important area for intervention that has yet been adequately investigated. A diagnosis of AD or MCI can mean considerable heterogeneity in terms of age, comorbidity, course of illness, cognitive impairment, functional limitations and abnormalities of behaviour. This study enables a consideration of the relation, if any, between frailty and these domains of clinical heterogeneity in a group of patients with AD and MCI.
PUBLISHED
Keywords: Alzheimer's disease